Roman Antiquity in Early Byzantine Antiquarian Tradition: John the Lydian and John Malalas - Marina Sinitsa (Античная древность и средние века, 2019)
The paper examines themes and motifs related to the history of ancient Rome, in the works of early Byzantine authors of 6th century AD. John the Lydi-an and John Malalas. Interest in classical antiquity, at this time already definitely formed as a so-called antique tradition in the first reception. This tradition was focused on the interest is not so much to history as such, as to some interesting details or specific facts and realities of the pagan past that for one reason or an-other might be interested in reading the audience Empire the 6th century AD. Early Byzantine antiquarianism, in the end, shows the true realities of classical antiquities, and presents them with some distorted optics of medieval shift in the perception of the past.